The Determining Factors in Influencing Customer’s Loyalty: A Financial Approach - Hanafi, Syafiq Mahmadah (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2021)
The research aims to evaluate customers’ loyalty to Sharia banking related to internal and external factors of the financial performance approach. A loyalty is depicted with Third-Party Savings deposited in Sharia banking. This study employed Autoregressive-Distributive Lag (ARDL) to explore the short period and the long period from variables’ relationships. The findings reveal that profit-sharing, administration fee, the interest rate of a conventional bank, inflation, and the total number of accounts (NOA) had significant effects on Third-Party Saving (TPS). They imply that the customer’s loyalty is internally established if there is a higher profit sharing in savings, lower administration fees, and total supplementary accounts. Yet, it is formed by external incentives, i.e., a lower interest rate of conventional banking and inflation.